Green supplier development for manufacturing industry - Wan Mahmood, Wan Hasrulnizzam; YAAKOB, MOHD YUHAZRI; Tukimin, Rahayu; Mohamed, Norhafiza (Penerbit UTeM Press, 2024)
A good relationship between manufacturers and a competent network of suppliers is required. Manufacturing enterprises may engage through the green supplier development program. The book will guide in ide in seeking the opportunity to implement a green supplier program. It will help improve sustainability and responsive performance of manufacturing enterprises.